Advanced processor selection guidance system for optimal computing performance using AHP-profile matching - Winardi, Slamet; Gumelar, Agustinus Bimo; Zulkifli, Che Zalina; Salmanarrizqie, Ageng; Suryo, Philipus (Jurnal Ilmiah Kursor, 2025)
The increasing complexity of modern processors and rapid advances in computing technology pose significant challenges for users seeking to select the optimal processor to satisfy their specific requirements. The " Processor Selection with AHP-Profile Matching: Implementation and Performance Analysis" addresses this problem by providing a structured, evidence-based approach to processor selection. This system integrates the Analytic Hierarchy Process (AHP) and profile matching algorithms to evaluate and rank processors based on parameters such as brand, price, socket type, thermal design power (TDP), core count, thread count, clock speed (GHz), DDR compatibility, and PCIe version. User inputs were collected and analyzed using the AHP to determine the relative importance of each criterion. Profile matching aligns user requirements with optimal processor configurations in a database. Results are presented through a comparative analysis that highlights each processor's strengths and limitations. Compatibility checks ensure seamless integration with existing hardware. The results indicate an accuracy of 81% with AHP alone and 91% with the combined AHP-Profile Matching approach. The proposed system significantly improves decision-making efficiency by providing a robust, user-centric processor selection approach and optimizing computational performance.